Anti-CD3 antibody visilizumab is not effective in patients with intravenous corticosteroid-refractory ulcerative colitis. Issue 11 (14th October 2010) - Sandborn, William J; Colombel, Jean Frederic; Frankel, Matthew; Hommes, Daan; Lowder, James N; Mayer, Lloyd; Plevy, Scott; Stokkers, Pieter; Travis, Simon; Van Assche, Gert; Baumgart, Daniel C; Targan, Stephan R
Abstract : Background and aims: Pilot studies with visilizumab, a humanised monoclonal antibody to CD3, suggest efficacy for corticosteroid-refractory ulcerative colitis (UC). A placebo-controlled trial was warranted. Methods: A randomised, double-blind, placebo-controlled study evaluated the efficacy of visilizumab induction treatment in 127 patients with severely active UC despite treatment with ≥5 days of intravenous corticosteroids. Patients received placebo or visilizumab 5 μg/kg intravenously on days 1 and 2. Corticosteroids were tapered according to disease activity. Patients were followed up for 90 days. The primary end point was induction of response at day 45. Secondary end points included remission and mucosal healing at day 45, symptomatic response at day 15 and colectomy. Results: Response at day 45 occurred in 55% of patients receiving visilizumab compared with 47% of those who received placebo (p=0.475). Remission at day 45 occurred in 8% of patients receiving visilizumab compared with 9% of those who received placebo (p=0.704). Mucosal healing at day 45 occurred in 29% of patients receiving visilizumab compared with 26% of those who received placebo (p=0.799). Symptomatic response at day 15 occurred in 82% of patients receiving visilizumab compared with 74% of those who received placebo (p=0.244). Colectomy was performed in 18% of patients receiving visilizumab compared with 7% of those who received placebo (p=0.130). Cardiac disorders and vascular disorders occurred more frequently in the patients who received visilizumab. Conclusion: Visilizumab at a dose of 5 μg/kg for two consecutive days was not effective for severe, corticosteroid-refractory UC and was associated with increased cardiac and vascular adverse events. (Registered at http://www.clinicaltrials.govNCT00279422/ ).